Estimasi Emisi Metana (CH4) pada Ternak Sapi Potong di Kabupaten Bengkulu Utara. - yurike, yurike (Buletin Peternakan Tropis, 2024)
This research aims to analyze estimates of methane (CH4) emissions in beef cattle in North Bengkulu Regency, as well as factors that influence these emissions based on meta-analysis studies. The research method uses a meta-analysis approach. The data used is secondary data from the North Bengkulu Regency Central Statistics Agency and literature studies from various journals. Calculation of methane emissions is carried out using the Tier 1 method based on the Intergovernmental Panel on Climate Change (IPCC). The reason for using the Tier 1 method is that specific data regarding emissions from beef cattle farms in North Bengkulu Regency is not yet available. The data obtained was then processed descriptively. The research results show that from 2019 to 2022, methane emissions from enteric fermentation of beef cattle in North Bengkulu Regency averaged 32.02 Gg CO2-eq/year and methane emissions from cow manure management averaged 0.68 Gg CO2- eq/year. It appears that there is a unidirectional relationship between the level of beef cattle population and the estimated value of the emissions it produces. Factors that influence methane emissions on beef cattle farms include the type of feed, number of livestock, manure management system, and medication administration. Collaboration between governments, livestock farmers and other stakeholders is needed to implement effective solutions to reduce the environmental impact of beef cattle farming and contribute to global climate change mitigation efforts.   Key words: Beef Cattle, Green House Gases, methane emissions   ABSTRAK Penelitian ini bertujuan untuk menganalisis estimasi emisi metana (CH4) pada ternak sapi potong di Kabupaten Bengkulu Utara, serta faktor-faktor yang mempengaruhi emisi tersebut berdasarkan studi meta analisis. Metode penelitian menggunakan pendekatan meta analisis. Data yang digunakan merupakan data sekunder dari Badan Pusat Statistik Kabupaten Bengkulu Utara dan studi literatur dari berbagai jurnal. Penghitungan emisi metana dilakukan dengan menggunakan metode Tier 1 berdasarkan Intergovernmental Panel on Climate Change (IPCC). Alasan penggunaan metode Tier 1 adalah belum tersedianya data spesifik mengenai emisi dari peternakan sapi potong di Kabupaten Bengkulu Utara. Data yang diperoleh kemudian diolah secara deskriptif. Hasil penelitian menunjukkan pada tahun 2019 hingga 2022, emisi metana dari fermentasi enterik sapi potong di Kabupaten Bengkulu Utara rata-rata sebesar 32,02 Gg CO2-eq/tahun dan emisi metana dari pengelolaan kotoran sapi rata-rata sebesar 0,68 Gg CO2-eq/tahun. Terlihat ada hubungan searah antara tingkat populasi sapi potong dengan nilai estimasi emisi yang dihasilkannya. Faktor-faktor yang mempengaruhi emisi metana pada peternakan sapi potong diantaranya jenis pakan, jumlah ternak, sistem pengelolaan kotoran, dan pemberian obat-obatan. Diperlukan kolaborasi antara pemerintah, peternak, dan pemangku kepentingan lainnya untuk mengimplementasikan solusi-solusi yang efektif guna mengurangi dampak lingkungan dari peternakan sapi potong dan berkontribusi pada upaya mitigasi perubahan iklim secara global.   Kata kunci: Sapi Potong, Gas Rumah Kaca, Emisi Metana